Problems and Possibilities of Implementing Resocialisation in Lithuanian Prisons - Aleknevičienė, Jolanta; Kalinauskaitė, Ignė (Socialinė teorija, empirija, politika ir praktika, 2023)
Lithuania‘s strategic documents point out that the main purpose of the execution of sentences is the resocialisation of convicts. The article analyses the problems and possibilities of the implementation of resocialisation of convicts in Lithuanian prisons today, based on the ideas of positivist and critical criminology. The research comprised an analysis of scientific literature and strategic documents in Lithuania, and an empirical qualitative study, which included twenty semistructured interviews with Lithuanian prison staff and experts from the penitentiary system. The data analysis was based on thematic analysis. The study reveals that resocialisation as a priority becomes a secondary goal of imprisonment during implementation, pursued in a demotivating and desocialising prison environment and punitive culture. The gap between the prison‘s stated objectives of resocialising prisoners and the human and financial capacity to achieve this is noted. Positivist and critical criminology ideas broaden the perception and analysis of resocialisation as a phenomenon and make it possible to rethink the functional and institutional distinction between the punishment of convicted persons and their treatment, assistance, and motivated personal transformation as different activities. The study suggests that the success of resocialisation of an individual requires the disaggregation and implementation of the stages of resocialisation, not only in prison but also in institutions that focus on helping without retribution and punishment.